1983
DOI: 10.1080/00288233.1983.10427018
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in ewe lambs and its effect on 2-year-old performance

Abstract: Reproductive performance was studied in 1-and 2-year-old Romney and Border Leicester x Romney ewes. Control lambs were joined with vasectomised rams, and the remainder were joined with entire rams for 5 weeks. Fertility, growth rate, and weaning rate were higher in crossbred ewe lambs, and birth rank effects were small. Conception rate to first service was negatively related to liveweight gain over joining. Weaning rate (57070 lambs weaned/ewe joined) was lower than normally expected from adult ewes. Lamb surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 9 publications
4
8
0
1
Order By: Relevance
“…In support of the present findings, Moore et al (1989) reported that lamb survival to weaning was not affected by hogget pasture allowance in pregnancy when daily herbage allowances ranged from 2-10 kg DM. Singleton-and twin-lamb survival rates to weaning were 76.2 and 61.7%, respectively in the present study which were similar to those previously reported by McMillan (1983), McMillan & McDonald (1983), and Moore et al (1989). McMillan (1983) and McMillan & McDonald (1983) stated that optimal survival rates for lambs born to hoggets were achieved in the birthweight range of 3.3-4.1 kg.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In support of the present findings, Moore et al (1989) reported that lamb survival to weaning was not affected by hogget pasture allowance in pregnancy when daily herbage allowances ranged from 2-10 kg DM. Singleton-and twin-lamb survival rates to weaning were 76.2 and 61.7%, respectively in the present study which were similar to those previously reported by McMillan (1983), McMillan & McDonald (1983), and Moore et al (1989). McMillan (1983) and McMillan & McDonald (1983) stated that optimal survival rates for lambs born to hoggets were achieved in the birthweight range of 3.3-4.1 kg.…”
Section: Discussionsupporting
confidence: 82%
“…Singleton-and twin-lamb survival rates to weaning were 76.2 and 61.7%, respectively in the present study which were similar to those previously reported by McMillan (1983), McMillan & McDonald (1983), and Moore et al (1989). McMillan (1983) and McMillan & McDonald (1983) stated that optimal survival rates for lambs born to hoggets were achieved in the birthweight range of 3.3-4.1 kg. In the present study the average birthweights of all nutritional treatments were within this range.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the relative size of the differences, when apparent, was relatively small (maximum of 3 kg weight and 0.2 condition score). The results of previous studies support the negative impact of hogget breeding on two-tooth live weight (Keane 1974;Baker et al 1981;McMillan & McDonald 1983). However, other studies found that the live weight effect was no longer apparent in later years (Cannon & Bath 1969;Dyrmundsson 1973;Baker et al 1978Baker et al , 1981.…”
Section: Discussionsupporting
confidence: 79%